Important Nonparental Adults as an Academic Resource for Youth. (May 2013) - Farruggia, Susan P.; Bullen, Pat; Davidson, Joy
This study examined the associations between various sources of social support and academic achievement. Participants were 313 ethnically diverse students attending a low-income intermediate school in New Zealand (mean age = 11.96 years). They reported on the presence and nature of a relationship with a very important nonparental adult in their lives (VIP), and on parent, peer, and VIP warmth and acceptance. Indicators of academic achievement (standardized tests) were also gathered from the school. Results showed that 62% of the youth reported the presence of at least one VIP in their lives, and there was a significant, positive correlation between VIP presence and the majority of academic achievement variables. VIP warmth was uniquely associated with all achievement variables, while parent and peer warmth were nonsignificant in the presence of VIP warmth. The results indicate that VIPs are an important resource for youth who are at risk of low achievement.